Kemampuan Dasar-Dasar Akuntansi Dan Keberlanjutan Studi Mahasiswa di Program Studi Akuntansi di Lingkungan Perguruan Tinggi Muhammadiyah (PTM) Jakarta - Henny Mulyati (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
The purposes of this study are (1) to know and to analyze if competences of basic accounting influencing the sustainibilty study of students doing the accounting course in muhammadiyah's high educational institution in Jakarta; and (2) to analyze how basics accounting competences influencing the sustainibilty study of students doing the accounting course in muhammadiyah's high educational institution in Jakarta. From this study shown that (1) hypothesis of determinant cooeficient in basics accounting subject to passing grade (IPK) is 0.8% and others influenced by 99,2% from another factors i.e not discussed in this study.; (2) hypothesist of determinant cooeficient of grade of basics accounting subjects to sustainilility study at study times shown the value of 0.5% and others influenced by 99.5% from another factors i.e not discussed in this study.